Climate Resilient Agriculture Practices - The Future of Farming - Patel, Jitendra; Kumar, G Shiva (Plant Science Today, 2023)
Climate-resilient agriculture (CRA) harnesses the intrinsic roots of agricultural and oxen production systems to generate increased long-term yields and farm income through sustainability. This review paper aims to draw attention to climate-resilient farming practices for medicinal plants and other cereal crops. There are several techniques and strategies that can be used to adapt to climate change, including yield-tolerant strains in poultry and cattle, Feed administration, irrigation, Agro-consulting and clay organic carbon. Governmental climate change adaptation programs such as the National Action Plan on Climate Change (NAPCC), the Pradhan Mantri Krishi Sinchayee Yojana (PMKSY), the Indian Council of Agricultural Research (ICAR), the Paramparagat Krishi Vikas Yojana and the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) continue to be implemented. Agriculture in India offers a living for the bulk of the populace and should never be disregarded. Increased demand for quantity, healthful food and diversity, as well as globalization effects and rising median income, would be revealed by India's growing population, globalization effects and increasing median income. Nutrient deficiencies in Indian soils, Imbalanced fertilizer application and Lack of Nitrogen-fixing crops have all caused significant climatic stress in India and the rest of the world. Various programs and policies, such as the Soil Health (Vitality) Card Scheme, are in place to improve fertilizer use efficiency. This cultivation practice pays attention to maintaining the environmental balance and bio-dynamization of agricultural systems so that ethical yield can be obtained.